2020
DOI: 10.3390/nu12113243
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Euglena gracilis Intake on Mood and Autonomic Activity under Mental Workload, and Subjective Sleep Quality: A Randomized, Double-Blind, Placebo-Controlled Trial

Abstract: While the human body maintains homeostasis by altering the balance in the autonomic nervous, endocrine, and immune systems, a prolonged imbalance in these systems can result in physical and mental symptoms, including a decline in sleep quality and work efficiency. Euglena gracilis (Euglena) is a single-celled microalga with the properties of both plants and animals and contains abundant nutrients, such as vitamins, minerals, amino acids, and fatty acids, which have various beneficial health effects. This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…The paramylon has also been shown to have a renoprotective effect in chronic kidney disease in a rodent [ 191 ]. Intake of E. gracilis also has positive effects on mood, autonomic activity, and sleep quality [ 192 ]. Finally, paramylon has been shown to accelerate wound healing in the skin when being applied as a film dressing [ 193 ].…”
Section: Euglena As Commercial Product and A Source For Medi...mentioning
confidence: 99%
“…The paramylon has also been shown to have a renoprotective effect in chronic kidney disease in a rodent [ 191 ]. Intake of E. gracilis also has positive effects on mood, autonomic activity, and sleep quality [ 192 ]. Finally, paramylon has been shown to accelerate wound healing in the skin when being applied as a film dressing [ 193 ].…”
Section: Euglena As Commercial Product and A Source For Medi...mentioning
confidence: 99%
“…Moreover, microalgal glucans exhibit antibacterial and cholesterol-lowering action and are effective in colorectal cancer treatment [ 59 ]. Recently, Nakashima et al [ 32 ] studied the effects of E. gracilis biomass on mental health and sleep in stressed and overworked individuals.…”
Section: Therapeutic Potential Of Microalgae In Sleep and Mood Regula...mentioning
confidence: 99%
“…Furthermore, chronic stress is associated with depression and inflammation, and is an indicator for insomnia [ 11 , 60 ]. A 12-week clinical trial revealed that a daily dose of 500–1000 mg of Euglena had calming effects on the sympathetic nervous system and therefore promoted a more relaxed body state [ 32 ]. Similarly, the same dose of Euglena promoted mental wellbeing.…”
Section: Therapeutic Potential Of Microalgae In Sleep and Mood Regula...mentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to other β-1,3-glucans, paramylon has a variety of health benefits, such as anti-obesity effects ( 13 ), suppression of atopic dermatitis ( 14 ), anti-HIV effect ( 15 ), and modulation of immune functions ( 16 19 ). Clinical trials have also shown that continuous intake of Euglena improves sleep quality ( 20 ). As it is involved in the regulation of sleep, it may be involved in clock regulation; however, no reports have been published examining whether Euglena or paramylon is involved in the regulation of the circadian clock.…”
Section: Introductionmentioning
confidence: 99%